ON Modified (α-η)-Contractive Mappings - Marwan Amin Kutbi; Muhammad Arshad; Aftab Hussain (Abstract and Applied Analysis)
Hussain et al. (2013) established new fixed point results in complete metric space. In this paper, we prove fixed point results of α-admissible mappings with respect to η, for modified contractive condition in complete metric space. An example is given to show the validity of our work. Our results generalize/improve several recent and classical results existing in the literature.